(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores methodological principles for fostering students’ technical creativity through the STEM approach, specifically in the context of physics education. It outlines strategies for integrating science, technology, engineering, and mathematics to enhance hands-on learning and problem-solving. The article analyzes existing literature, presents practical styles of teaching, and discusses the effectiveness of the STEM approach in nurturing innovation among students. Findings indicate that well-designed STEM-based physics instruction significantly boosts students’ creative and technical thinking.